واقع ظاهرة التدخين وأثرها في حياة الاسرة دراسة ميدانية في محافظة اللاذقية - حيدر عزالدين (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يهدف البحث إلى التعرف على واقع انتشار ظاهرة التدخين محافظة اللاذقية، مسبباتها، ومدى تأثير هذه الظاهرة في حياة الاسرة. تم اختيار عينة عشوائية بسيطة تضم 385 من البالغين في محافظة اللاذقية وقد توصل الباحث إلى جملة من النتائج أهمها هي التالية: نسبة مدخني السجائر تقدر بـ 40.7% من السكان في محافظة اللاذقية مقابل 38.8% لمدخني الأركيلة. يوجد أثر ذو دلالة احصائية للنوع في تدخين السجائر، فسبة تدخين النساء أقل بشكل جوهري من نسبة تدخين الذكور. لا يوجد أثر ذو دلالة احصائية للنوع في تدخين الأركيلة. يوجد أثر ذو دلالة احصائية لمستوى التعليم في تدخين السجائر، حيث يوجد فرق معنوي في تدخين السجائر بين حملة الشهادة الثانوية ومن يحملون الشهادة الاعدادية أو أقل. لا يوجد أثر ذو دلالة احصائية لمستوى التعليم في تدخين الأركيلة. يوجد أثر ذو دلالة احصائية للعمر في تدخين السجائر، فنسبة مدخني السجائر ترتبط بعلاقة طردية مع العمر. يوجد أثر ذو دلالة احصائية للعمر في تدخين الأركيلة، فنسبة مدخني الأركيلة ترتبط بعلاقة عكسية مع العمر. توجه الاسرة في العينة حوالي الـ 20.6% من دخلها للإنفاق على التدخين. يوجد لإنفاق الأسرة على تدخين السجائر أو الأركيلة أثر معنوي في مستوى معيشة الاسرة. يوجد لترافق الإنفاق على تدخين السجائر مع الإنفاق على الأركيلة أثر معنوي في مستوى معيشة الاسرة. Our research aims to understand the real perspective of smoking phenomena, Study the causes and the economic effects of this phenomena on the life of families in the Governorate of Latakia. We studded a simple probability sample of 385 adults from Leticia Governorate to test proposed hypothesizes. The results of our study indicate the following: The percent of Smokers of cigarette in the governorate of Latakia is 40.7% in opposite 38.8% of smoking hookah. There is a significant deference in smoking cigarette according to Gender. Female are the less smoking of cigarettes. There is no significant deference in smoking hookah according to Gender. There is a significant deference in smoking cigarette according to education level. Persons in secondary education level are less smoking than essential level. There is no significant deference in smoking hookah according to education level. There is a significant deference in smoking cigarette according to person’s age. Smoking cigarette has a positive correlation with person’s age. There are a significant deference in smoking hookah according to person’s age. Smoking hookah has a negative correlation with person’s age. 8. Tabaco expenditure of families in the Sample is 20.6% of families income. Smoking hookah or cigarette separately or both hookah and cigarette together has a significant impact on the Family’s life level.